Development of ipilimumab: a novel immunotherapeutic approach for the treatment of advanced melanoma. (17th June 2013) - Wolchok, Jedd D.; Hodi, F. Stephen; Weber, Jeffrey S.; Allison, James P.; Urba, Walter J.; Robert, Caroline; O'Day, Steven J.; Hoos, Axel; Humphrey, Rachel; Berman, David M.; Lonberg, Nils; Korman, Alan J.
Abstract : The immunotherapeutic agent ipilimumab has helped address a significant unmet need in the treatment of advanced melanoma. Ipilimumab is a fully human monoclonal antibody that targets cytotoxic T‐lymphocyte antigen‐4 (CTLA‐4), thereby augmenting antitumor immune responses. After decades in which a number of clinical trials were conducted, ipilimumab was the first therapy to improve overall survival in a randomized, controlled phase III trial of patients with advanced melanoma. These results led to the regulatory approval of ipilimumab at 3 mg/kg for the treatment of unresectable or metastatic melanoma. More than 17, 000 patients worldwide have received ipilimumab, either as a commercial drug at 3 mg/kg or in clinical trials and expanded access programs at different doses. Consistent with its proposed mechanism of action, the most common toxicities associated with ipilimumab therapy are inflammatory in nature. These immune‐related adverse events were mostly reversible when effective treatment guidelines were followed. Importantly, long‐term follow‐up of patients who received ipilimumab in a phase III trial showed that 24% survived at least two years, and in phase II studies, a proportion of patients survived at least five years. Evaluation of ipilimumab is ongoing in the adjuvant setting for melanoma, and for advanced disease in nonsmall cell lung, small cell lung, prostate, ovarian, and gastric cancers.